2021
DOI: 10.1101/2021.10.17.21265121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced seroconversion in children compared to adults with mild COVID-19

Abstract: Importance: The immune response in children with SARS-CoV-2 infection is not well understood. Objective: To compare seroconversion in children and adults with non-hospitalized (mild) SARS-CoV-2 infection and to understand the factors that influence this. Design: Participants were part of a household cohort study of SARS-CoV-2 infection. Weekly nasopharyngeal/throat swabs and blood samples were collected during the acute and convalescent period following PCR diagnosis for analysis. Setting: Participants were re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Several studies from Hong Kong, Australia and the United States have shown impaired humoral and cellular immune responses in children exposed to SARS-CoV-2 [ 10 , 26 , 76 , 105 ]. This agrees with our data showing impaired generation of T cell memory responses in children compared to adults.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from Hong Kong, Australia and the United States have shown impaired humoral and cellular immune responses in children exposed to SARS-CoV-2 [ 10 , 26 , 76 , 105 ]. This agrees with our data showing impaired generation of T cell memory responses in children compared to adults.…”
Section: Discussionmentioning
confidence: 99%
“…Another unavoidable limitation includes the possibility that the uninfected control group is contaminated by children who have been infected with SARS-CoV-2 but who were not tested or who did not seroconvert. 40 Further, studies that evaluate a single time point might miss transitory or intermittent symptoms of long COVID. Finally, the range and the number of symptoms sought in studies vary considerably and some studies have been criticized for evaluating certain key symptoms.…”
mentioning
confidence: 99%
“…This is in accordance with other studies, where children and adults with confirmed COVID positivity showed greater seropositivity. [ 10 20 ] The report of a recent survey conducted in our state also showed a seroconversion of more than 90% in children who had a history of COVID 19 positivity. [ 14 ] The delta variant, which was the predominant strain circulating in the community at the time of the study, may be the reason for the higher proportion of seroconversion.…”
Section: Discussionmentioning
confidence: 88%